Child Nutrition Health Services Centered on Primary Health Care To Reduce Stunting Incidence - Ni Putu Ayu Krisna Yuniastuti; I Kadek Adi Paramartha (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Stunting is a growth and development disorder that is characterized by a short body condition that exceeds the deficit (-2) standard deviation below the median height line by measuring the height for the child's age, through the child's height curve. Objectives: The purpose of this study was to determine nutritional services in primary health care to reduce the incidence of stunting. Research Metodes: The method used in writing this article uses a literature review through the Google Scholar database. Results: The results obtained are that in theory the implementation of the program can be carried out properly and continuously, but in the field it is not necessarily able to be implemented properly. Many factors can affect the implementation of nutrition services in Primary Health Care, but broadly it is divided into three factors, namely Provider, User and Program factors. Conclusion: Nutrition services in Primary Health Care should focus on providing complete and continuous knowledge at the community level, regular checks on mothers and children on a regular basis, as well as interventions that must be at the individual and community level such as supplementary feeding and others.